Content analysis of male & female green preferences on thrift clothes - Faerrosa, Lady; Widiyasti, Baiq Dinna; Komala, Rina (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
Currently, consumer purchasing behavior has shifted towards more environmentally friendly consumption such as thrift clothes, but literature regarding differences in male and female consumer preferences for thrift clothes is still limited. Therefore, the aim of this research is to explore differences in male and female consumer preferences for thrift clothes in Indonesia. The method used in this research is content analysis of data obtained online via Quora. The research results show that female consumers' preferences for thrift clothes are not limited to everyday clothes, but also formal clothes or work clothes. Likewise with male consumers. However, differences can be seen in terms of their concern for the environment, where female consumers are more numerous and more eager to show their concern for the environment by purchasing thrift clothing which is considered more environmentally friendly. This knowledge can provide a knowledge base for marketers of green products such as thrift clothes to develop marketing strategies that are more suited to female consumers in order to be able to improve their marketing performance in terms of increasing sales and increasing the number of consumer engagements.